Third Year Hon. Mention, Family and Freedom: A Study of Terentia and ‘Turia’: HIST 3160, Women and Gender in Ancient Greece and Rome. CD: Angela Hug. - Flavelle, Lex (Noteworthy: The LA&PS Writing Prizes, 2023)
This is a maturely considered essay that reviews the status of women citizens of Rome by means of two first-century BCE texts: the orator Cicero’s letters to his wife Terentia and the anonymous Laudatio Turiae. The essay is finely aware of the limitations of the evidence of which its case is based, but it perhaps more modest that it needs to be about the strength of its argument. The available evidence is employed with great care and subtlety to argue in a wholly persuasive way for the recognition that, for some women at least, greater agency in the public sphere was available than is conventionally allowed. The essay makes frequent and fluent use of both its primary and secondary sources and integrates its citations with a grace not always seen in the works of far more senior scholars.